Issues of the 2024 Presidential Candidates in Online News Texts: Critical Discourse Analysis of the Teun A Van Dijk Model - Surya R, Yusran; Jufri, Jufri; Usman, Usman (Journal of Asian Multicultural Research for Social Sciences Study, 2023)
The discourse on the 2024 presidential candidate issue is a discourse formed by the practice of power which implies certain goals. Therefore, media discourse that reports on the 2024 presidential candidate issue is an issue or problem that contains critical languages or expressions. This research is important to find out the purpose or intention of the presidential candidate issue which reports on popular figures who have a major influence on social change and the progress of the country in the future. The purpose of this study is to analyze news texts about presidential candidates using the text dimensions of the Teun A. van Dijk model in the form of macro structure, super structure, and micro structure which are modified with the Jufri model. The type of method used is qualitative with a qualitative descriptive design that describes aspects of the text dimensions of the discourse structure, the data used is written text on the online news media CNN Indonesia, Jawapos.com, and Kompas.com. The results of this study are to describe the description and interpretation of the aspects of text dimensions in the form of macro structure, super structure, and micro structure which are then explained in the form of actions or actions that have a specific purpose. This research is useful for making a theoretical contribution and providing a conceptual overview that can inspire researchers or students who focus on the study of critical discourse analysis and can be implemented in critical discourse courses.